Satisfying Individual Desires or Moral Standards? Preferential Treatment and Group Members’ Self-Worth, Affect, and Behavior - Thau, Stefan; Tröster, Christian; Aquino, Karl; Pillutla, Madan M.; De Cremer, David 1972- (2013)
We investigate how social comparison processes in leader treatment quality impact group members’ self-worth, affect, and behavior. Evidences from the field and the laboratory suggest that employees who are treated kinder and more considerate than their fellow group members experience more self-worth and positive affect. Moreover, the greater positive self-implications of preferentially treated group members motivate them more strongly to comply with norms and to engage in tasks that benefit the group. These findings suggest that leaders face an ethical trade-off between satisfying the moral standard of treating everybody equally well and satisfying individual group members’ desire to be treated better than others.
Keywords: Affect; Status; Social comparison; Norm compliance; Leadership; Group value model